Chill sensitiveness and thermal analysis parameters relationship in hypo-eutectic, Ca and Ca-La inoculated commercial grey cast irons - RIPOSAN, IULIAN (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
Previous experiments shown a specific distribution of Al, La and Ca on the section of complex (Mn,X)S compounds, found as major nucleation sites for graphite flakes in low-S cast irons (< 0.03%S), and a possible contribution of La to improve their capacity to nucleate graphite, avoiding carbides formation. In the present work, standard thermal [cooling curves] investigations are undertaken to explore Ca and La-Ca bearing FeSi alloys inoculation effects [10 measurements for each inoculant], in 3.7 – 3.8%CE and optimum S and Mn relationship [0.046 – 0.056%S, (%Mn) x (%S) = 0.024 – 0.029]. Representative temperatures on the cooling curves and under-cooling degrees referring to the meta-stable eutectic temperatures are determined and correlated with the chill [carbides/graphite formation sensitiveness], in different solidification conditions [cooling modulus, wedge shape castings, resin sand mould]. Supplementary addition of La to Ca-bearing inoculants has limited, but specific benefits in these cast irons: lower eutectic recalescence and of the maximum recalescence rate, higher GRF1 and lower GRF2 graphitizing factors and lower value of the first derivative at the end of solidification. Consequently, it results a premise for lower shrinkage sensitiveness and lower chill (carbides) sensitiveness, especially at the highest solidification cooling rate (thin wall castings).